Planned relocation in Asia and the Pacific - Connell, J; Coelho, S (Refugee Studies Centre, University of Oxford, 2018)
Promising policy developments are underway in Asia and the Pacific to address climate and disaster-related displacement, yet the deeper governance structures required to embed protection are not yet in place, especially for planned relocation. There needs to be greater emphasis on assisting governments to set up inter-ministerial structures equipped to deal with the complex cross-cutting issues that planned relocation involves.